Competition of State Powers During the COVID-19 Pandemic - Birmontienė, Toma; Miliuvienė, Jolita (Teisė, 2022)
The aim of this article is to analyse what kind of powers deriving from the rule of law can be extended to public authorities in response to the global COVID-19 pandemic, what is the balance of powers between the legislative and the executive whilst imposing measures controlling the virus, and what role is played by the constitutional courts whilst deliberating on constitutional disputes involving public authorities.